2013
DOI: 10.3126/kumj.v10i3.8015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Hypertension Among People Aged 50 years and more in Banepa Municipality, Nepal

Abstract: BackgroundHypertension is a cardiovascular disorder rapidly emerging as a major public health problem in developing countries and is the most widely recognized modifiable risk factor for cardiovascular diseases. ObjectiveThe objective of this study was to find out the prevalence and associated risk factors with hypertension among people aged 50 years and more in Banepa Municipality, Kavre, Nepal. MethodsIt is a cross-sectional, population based study which was carried out in Banepa Municipality from May 15 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
20
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 16 publications
11
20
4
Order By: Relevance
“…These associations are well established in various studies conducted at national and international level. 9,10,12,25,[27][28][29][30][31][32][33] Hypertension prevalence increased with advancing age (Table 1) in this study which is consistent with findings from number of other studies. [27][28][29][30][31][32][33] Majority of the respondents (152) in this study were female.…”
Section: -14supporting
confidence: 90%
See 3 more Smart Citations
“…These associations are well established in various studies conducted at national and international level. 9,10,12,25,[27][28][29][30][31][32][33] Hypertension prevalence increased with advancing age (Table 1) in this study which is consistent with findings from number of other studies. [27][28][29][30][31][32][33] Majority of the respondents (152) in this study were female.…”
Section: -14supporting
confidence: 90%
“…30,31,37 Although, surplus of evidence from number of research studies points out the possibility of strong association between gender difference and prevalence of hypertension, debates still exists for no such association as well. 9,30,31,36 Family history of hypertension is a well-known risk factor of hypertension, yet in this study no significant association (p=0.080) was found between heredity and hypertension. However, the prevalence of hypertension was found to be slightly higher among those with family history of hypertension (29.4%) compared to those who did not have a family history of hypertension (18%).…”
Section: -14contrasting
confidence: 61%
See 2 more Smart Citations
“…Particularly, a moderate increase in body mass index, makes South Asians more prone to develop diabetes and cardiovascular diseases. Our study found about 60% of the study populations were obese according to their Body Mass Index (BMI) which also put them at risk of developing cardiovascular disease which is little higher as compared to a study done in Kavre, 17 which showed 54.4%. High WC was prevalent in 66.7% of total respondent which was higher than some other studies done in Nepal but different population groups.…”
Section: Discussioncontrasting
confidence: 59%